From Fei Xiaotong to Shi Zhengyi: The Chinese Economic Anthropology Pioneers’ Academic Essentials - Tian, Robert Guang (Advances in Social Sciences Research Journal, 2021)
In China, economic anthropology started relatively later compared with that in the West; however, under the guidance of Marxist theory and based on the needs of China's economic development, it gradually formed unique advantages in its development process. In China's economic and social development practice, Fei Xiaotong and Shi Zhengyi, among other pioneers, creatively applied the economic anthropological paradigm to solve the specific issues, starting from the local characteristics, and completed some excellent academic results. This paper probes and analyzes the scholarly contributions of the pioneers of Chinese economic anthropology; especially, it takes Marxist economics as the starting point to examine Professor Shi Zhengyi's theoretical contributions to the development of Chinese economic anthropology and its practical significance.